2004
DOI: 10.1103/physrevb.70.134429
|View full text |Cite
|
Sign up to set email alerts
|

Giant phonon softening in the pseudogap phase of the quantum spin systemTiOCl

Abstract: Giant anomalies are found in the temperature dependence of Raman-active phonons in the quantum magnet TiOCl, suggesting the presence of an extended fluctuation regime. This regime coincides with a pseudogap phase identified in earlier NMR experiments. The observed large, local spin-gap is proposed to origin from coupled spin/lattice fluctuations. Below 100 K, in the long-range crystallographically distorted phase, a dimerized ground state with a smaller, global spin-gap of about 2⌬ spin Ϸ 430 K exists. This tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
78
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(92 citation statements)
references
References 20 publications
(36 reference statements)
14
78
0
Order By: Relevance
“…2͑a͔͒. In addition to these expected modes, TiOCl displays a broad peak in the c͑bb͒c polarization, centered at around 160 cm −1 at 300 K; a similar feature is observed in TiOBr as a broad background in the low frequency region at 100 K. As discussed for TiOCl, 13 these modes are thought to be due to pretransitional fluctuations. Upon decreasing the temperature, this "peaked" background first softens, resulting in a broad mode at T c2 ͓see Fig.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…2͑a͔͒. In addition to these expected modes, TiOCl displays a broad peak in the c͑bb͒c polarization, centered at around 160 cm −1 at 300 K; a similar feature is observed in TiOBr as a broad background in the low frequency region at 100 K. As discussed for TiOCl, 13 these modes are thought to be due to pretransitional fluctuations. Upon decreasing the temperature, this "peaked" background first softens, resulting in a broad mode at T c2 ͓see Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Afterward, through the analysis of Raman spectra, the crystal symmetry in the low temperature phases will be discussed, and in the final part, a comparison with the isostructural VOCl will be helpful to shed some light on the origin of the anomalous high energy scattering reported for TiOCl and TiOBr. 13,19 A. High temperature phase…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 This indicates strong coupling of the lattice to the electronic (spin or orbital) degrees of freedom. Indeed, LDA+U calculations for frozen lattice distortions corresponding to the relevant phonon modes have shown that the orbital ground state may switch from 3d xy to 3d xz,yz for sufficiently large amplitude.…”
Section: Polarization-dependent Photoemissionmentioning
confidence: 99%